Purification and characterization of trehalose phosphorylase from the commercial mushroom Agaricus bisporus - Wannet, Wim J.B.; Op den Camp, Huub J.M.; Wisselink, Hendrik W.; van der Drift, Chris; Van Griensven, Leo J.L.D.; Vogels, Godfried D. (Biochimica et biophysica acta, 1998)
Trehalose phosphorylase (EC 2.4.1.64) from Agaricus bisporus was purified for the first time from a fungus. This enzyme appears to play a key role in trehalose metabolism in A. bisporus since no trehalase or trehalose synthase activities could be detected in this fungus. Trehalose phosphorylase catalyzes the reversible reaction of degradation (phosphorolysis) and synthesis of trehalose. The native enzyme has a molecular weight of 240 kDa and consists of four identical 61-kDa subunits. The isoelectric point of the enzyme was pH 4.8. The optimum temperature for both enzyme reactions was 30°C. The optimum pH ranges for trehalose degradation and synthesis were 6.0–7.5 and 6.0–7.0, respectively. Trehalose degradation was inhibited by ATP and trehalose analogs, whereas the synthetic activity was inhibited by P i ( K i=2.0 mM). The enzyme was highly specific towards trehalose, P i, glucose and α-glucose-1-phosphate. The stoichiometry of the reaction between trehalose, P i, glucose and α-glucose-1-phosphate was 1:1:1:1 (molar ratio). The K m values were 61, 4.7, 24 and 6.3 mM for trehalose, P i, glucose and α-glucose-1-phosphate, respectively. Under physiological conditions, A. bisporus trehalose phosphorylase probably performs both synthesis and degradation of trehalose.